Effectiveness of an Individualized Diabetes Health Education Program Using Real-Time Continuous Glucose Monitoring in Improving Blood Glucose: A Pilot Interventional Study on Subjects with Prediabetes - Ma, Yuqi; Deng, Sisi; Xie, Wei; Weng, Minfang; Jia, Yeran (Diabetes, metabolic syndrome and obesity, 2025)
While lifestyle modification remains fundamental for prediabetes management, the potential added value of real-time continuous glucose monitoring (RT-CGM) in diabetes health education programs warrants investigation. This study evaluated whether an individualized diabetes health education program using RT-CGM could improve glycemic control compared to general dietary guidance in prediabetic individuals. In this randomized controlled trial conducted at Guangdong Provincial People's Hospital (initiated September 2022), we enrolled 41 adults (>18 years) with prediabetes, randomly assigning them to either: (1) RT-CGM group (n=20) receiving meal adjustments based on continuous glucose data and energy balance, or (2) control group (n=21) receiving adjustments based solely on energy balance. The study comprised two intensive 14-day education sessions (baseline and 1-year follow-up) with metabolic assessments (HbA1c, fasting blood glucose, BMI, lipid profile, and uric acid) conducted at baseline, 1-year, and 2-year timepoints. The RT-CGM group demonstrated significantly greater improvements in HbA1c compared to controls at both 1-year (p=0.007) and 2-year (p=0.033) follow-ups. Our findings suggest that incorporating RT-CGM into diabetes health education program can enhance glycemic control in prediabetic individuals compared to general dietary guidance alone. These results support the potential clinical utility of RT-CGM in prediabetes management strategies.